2012
DOI: 10.1111/j.1743-6109.2011.02541.x
|View full text |Cite
|
Sign up to set email alerts
|

Greater Resting Heart Rate Variability is Associated with Orgasms Through Penile–Vaginal Intercourse, but Not with Orgasms from Other Sources

Abstract: Introduction Resting heart rate variability (HRV), a marker of parasympathetic activity, is a predictor of health and longevity. Better erectile function is associated with greater resting HRV (assessed by high frequency power [HF]), and in both sexes, penile–vaginal intercourse (PVI) is the only sexual behavior consistently associated with indices of better physical and mental health, including greater resting HRV (assessed by standard deviation [SD] of heart rate [HR]). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 52 publications
7
35
0
9
Order By: Relevance
“…Greater parasympathetically-driven heart rate variability (associated with a broad range of indices of better health) is associated with greater frequency of PVI, but not of other sexual activities (Brody & Preut, 2003;Brody, Veit, & Rau, 2000;Costa & Brody, 2012a). This is consistent with a prepotent vagal output to vagal genital sensory input reflexive connection.…”
Section: Anatomical and Physiological Differences Between Vagina Cersupporting
confidence: 66%
See 1 more Smart Citation
“…Greater parasympathetically-driven heart rate variability (associated with a broad range of indices of better health) is associated with greater frequency of PVI, but not of other sexual activities (Brody & Preut, 2003;Brody, Veit, & Rau, 2000;Costa & Brody, 2012a). This is consistent with a prepotent vagal output to vagal genital sensory input reflexive connection.…”
Section: Anatomical and Physiological Differences Between Vagina Cersupporting
confidence: 66%
“…Levin (2012b) further states that for Brody and Costa (Brody, 2010; ''[C]litoral stimulation during PVI is said to negate any of the benefits that PVI-orgasm confers without this stimulation'' (p. 308). What has been found in the relevant empirical studies that compared vaginal orgasm with the orgasm obtained by clitoral masturbation during PVI, is that vaginal orgasm is associated with more secure attachment , less risk of inhibited sexual desire (Nutter & Condron, 1983), less use of immature psychological defense mechanisms , 2010b and greater resting heart rate variability (Costa & Brody, 2012a), whereas the same studies found that orgasm by clitoral masturbation is unrelated to attachment style, sexual desire and resting heart rate variability and is actually related to more use of immature defense mechanisms. Although it is possible that PVI still has benefits, even when associated with simultaneous clitoral masturbation, the evidence shows that it is specifically the orgasm provoked by penile-vaginal stimulation without simultaneous clitoral masturbation that has the most clearly favorable correlates.…”
Section: Anatomical and Physiological Differences Between Vagina Cermentioning
confidence: 99%
“…Another shared biomarker is low resting heart rate variability —a measure of autonomic nervous system (ANS) activity— which is a marker of depression and anxiety (Kemp, Quintana, Felmingham, Matthews, & Jelink, 2012; Kemp, Quintana, Gray, Felmingham, Brown, & Gatt, 2010), and has recently been found to predict female sexual arousal and orgasmic function (Costa & Brody, 2012; Stanton, Lorenz, Pulverman & Meston, 2015) and erectile dysfunction (Lee, Joo, Kim, Cho, Cho, Won & Choi, 2011). Serum markers of inflammation that are associated with depression (e.g., Ramsey et al, 2016) have also been found to predict erectile dysfunction (e.g., Vlachopoulos et al, 2006).…”
Section: Part 2: Evidence That Supports the Formation Of The Hypothesmentioning
confidence: 99%
“…Research further suggests that social support from high-quality relationships may be the protective mechanism against mortality (Holt-Lunstad et al, 2010). Similarly, frequency of sexual intimacy for individuals in relationships has been linked to greater mental and physical health outcomes, such as more general happiness and greater life satisfaction (Muise et al, 2016), greater heart variability (Costa & Brody, 2012), lower daily somatic symptoms (Stadler et al, 2012), reduced daily diurnal cortisol (Ditzen et al, 2008), and a more robust immune response (Charnetski & Brennan, 2004). However, to date, no studies have examined biomarkers of long-term health status such as telomere length.…”
Section: Introductionmentioning
confidence: 99%